Identificación y origen de inclusiones no metálicas en aceros - Baez, Juan Nicolás; Libanati, Cesar Mario; Vassallo, Daniel Irineo; Wortman, Oscar; Zaretsky, Z. (Comisión Nacional de Energía Atómica; Argentina, 1967)
Fil: Baez, Juan Nicolás Comisión Nacional de Energía Atómica; Argentina